Utilization of Cloud Computing Technology in Improving Data Efficiency of Startups - Ardi Azhar Nampira; Ahmad Syamsudin (Technologia Journal, 2025)
The development of digital technology encourages startups to look for efficient solutions in data management. One technology that is widely adopted is cloud computing, as it offers flexibility, cost efficiency, and scalability. However, there are not many studies that specifically examine its impact on data efficiency in startups in Indonesia. This research aims to analyze how the use of cloud computing improves operational efficiency and data management in startups, while identifying challenges and best practices in its implementation. The method used is a qualitative case study approach involving several startups using cloud services in Indonesia as the main informants. The results show that cloud adoption has a positive impact on accelerating data access, improving team collaboration, and IT cost efficiency. Cloud also provides added value in terms of data security and scalability. Nevertheless, obstacles such as limited human resources and dependence on service providers are still the main obstacles. In conclusion, cloud computing is proven to be a strategic solution in improving data efficiency in startups, as long as it is balanced with organizational readiness and the right implementation strategy.